Cubeb (Piper cubeba L.): nutritional value, phytochemical profiling and dermacosmeceutical properties - Drissi, Badr Eddine; Mahdi, Ismail; Ortaakarsu, Ahmet Buğra; Abdelfattah, Mohamed A. O.; Bakrim, Widad Ben; Khatib, Sohaib; Mahmoud, Mona F.; Bouissane, Latifa; Sobeh, Mansour (Frontiers in Nutrition, 2024)
Introduction Cubeb, Piper cubeba L., has been used for centuries in traditional medicine and culinary practices, with a wide range of biological and pharmacological activities. Objective Herein, we determined the phytochemical profile, mineral, fatty acids, and amino acid contents of P. cubeba berries and assessed the dermacosmeceutical properties of their water extract and essential oil (EO). These included assessing their antioxidant and antibacterial activities as well as their in vitro inhibitory activities against tyrosinase and elastase enzymes. In addition, molecular docking and molecular dynamics studies were performed on the major identified compounds of the EO. Results and discussion A total of forty-three compounds belonging to organic acids, phenolic acids and flavonoids were found in the water extract, while 36 volatile compounds were identified in the EO with Z-isoeugenol, dihydroeugenol, β-pinene, E-caryophyllene, and 1,8-cineole as major constituents. The berries were found to be rich in sodium and iron, have moderate zinc content along with low contents of total nitrogen, phosphorus, and potassium. Amino acid analysis revealed a considerable concentration of isoleucine and phenylalanine, whereas 11,14,17-eicosatrienoic acid and linoleic acid were identified as the major fatty acids. In the DPPH and FRAP assays, the water extract elicited considerable antioxidant activity compared to the reference compounds. Enzyme inhibitory assays revealed that the EO had a potential to inhibit tyrosinase and elastase enzymes with IC50 values of 340.56 and 86.04 μg/mL, respectively. The water extract and EO completely inhibited the bacterial growth at MIC of 50 mg/mL and 20%, respectively. At sub-MIC concentrations, the extract and the EO substantially reduced the biofilm formation by up to 26.63 and 77.77%, respectively, as well as the swimming and swarming motilities in a dose-dependent manner. Molecular docking and molecular dynamics showed that the five main components of P. cubeba EO could be the major contributors to the elastase and tyrosinase inhibitory effect. Conclusion This study emphasizes the promising potential of P. cubeba as a valuable source of natural compounds that can be utilized for the development of innovative pharmaceuticals, dietary supplements, and dermacosmeceutical agents.